2005
DOI: 10.4315/0362-028x-68.10.2224
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Shiga Toxin–Producing Escherichia coli in Beef Cattle

Abstract: A large number of Shiga toxin-producing Escherichia coli (STEC) strains have caused major outbreaks and sporadic cases of human illnesses, including mild diarrhea, bloody diarrhea, hemorrhagic colitis, and the life-threatening hemolytic uremic syndrome. These illnesses have been traced to both O157 and non-O157 STEC. In a large number of STEC-associated outbreaks, the infections were attributed to consumption of ground beef or other beef products contaminated with cattle feces. Thus, beef cattle are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
117
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(132 citation statements)
references
References 152 publications
6
117
1
1
Order By: Relevance
“…[9][10][11][12] All of the ready to eat food samples of our investigation were meat-based ready to eat foods. Some of them like sausage, salami and soup were Article produced in high temperature and therefore were free from any pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12] All of the ready to eat food samples of our investigation were meat-based ready to eat foods. Some of them like sausage, salami and soup were Article produced in high temperature and therefore were free from any pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that some pathogenic bacteria, including VTEC and Salmonella, can be transferred from hides to carcasses during processing (Elder et al 2000, Reid et al 2003, Hussein and Bollinger 2005. The prevalence of pathogens in cattle identified during the slaughter process has varied considerably in the previously described surveys (Bell 1997, Scanga et al 2000, Madden et al 2001, Barkocy-Gallagher et al 2003, Rivera-Betancourt et al 2004, Brichta-Harhay et al 2008, Bosilevac et al 2009.…”
Section: Discussionmentioning
confidence: 99%
“…However, samples were collected in winter and spring months. It was reported that in ruminants the prevalence of Escherichia coli O157:H7 is the highest in summer months and decreases in winter months 6,26 . Pathogenic STEC strains produce toxins that cause human illnesses and can produce other virulence factors that may increase the severity of illnesses.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is isolated from many animal species, it was reported that STEC O157 is largely hosted in cattle intestines without showing any symptoms 6 . It was reported that cattle beef, milk and the products obtained from them play an important role in the development of human STEC infections 1 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation